2012
DOI: 10.1155/2012/725061
|View full text |Cite
|
Sign up to set email alerts
|

The Two‐Variable (G/G, 1/G)‐Expansion Method for Solving the Nonlinear KdV‐mKdV Equation

Abstract: We apply the two-variable (, )-expansion method to construct new exact traveling wave solutions with parameters of the nonlinear ()-dimensional KdV-mKdV equation. This method can be thought of as the generalization of the well-known ()-expansion method given recently by M. Wang et al. When the parameters are replaced by special values, the well-known solitary wave solutions of this equation are rediscovered from the traveling waves. It is shown that the proposed method provides a more general powerful mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 35 publications
2
31
0
1
Order By: Relevance
“…As a pioneer work, Li et al [39] have applied the two-variable (G /G, 1/G)--expansion method and found the exact solutions of the Zakharov equations. Then Zayed and Abdelaziz [40,41] determined exact solutions of some nonlinear evolution equations. (1/G )-expansion method has rst been introduced by Yoku³ [42].…”
Section: Introductionmentioning
confidence: 99%
“…As a pioneer work, Li et al [39] have applied the two-variable (G /G, 1/G)--expansion method and found the exact solutions of the Zakharov equations. Then Zayed and Abdelaziz [40,41] determined exact solutions of some nonlinear evolution equations. (1/G )-expansion method has rst been introduced by Yoku³ [42].…”
Section: Introductionmentioning
confidence: 99%
“…The exact solutions to NLEEs help us to provide information about the structure of complex phenomena. As a key problem, finding their exact solutions is of great importance and it is actually executed through various efficient and powerful method, such as, the Hirota method [1], the Backlund transform method [2,3], the inverse scattering transform method [4], the Jacobi elliptic function expansion method [5][6][7], the truncated Painleve expansion method [8][9][10][11], the tanh function method [12][13][14][15], the Exp-function method [16][17][18][19][20][21][22], the ( ⁄ ) -expansion method [23][24][25][26][27][28][29][30], the improved ( ⁄ ) -expansion method [31][32], the two variable ( ⁄ , 1 ⁄ ) -expansion method [33,34], the first integral method [35] etc. The main concept of the ( ⁄ ) -expansion method is the exact solution of nonlinear NLEEs are revealed by a polynomial in one variable ( ⁄ ) in which = ( ) satisfies the second order ordinary differential equation (ODE) ( ) + ( ) + ( ) = 0, where and are constants.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of the polynomial can be evaluated by taking homogeneous balance between the highest-order derivatives and nonlinear terms in the given nonlinear PDEs, where the coefficient of the polynomial can be determined by solving a set of algebraic equations. Recently, Li et al [33] Density Dependent Fractional Diffusion Reaction Equation and Zayed et al [34] applied the two variable ( ⁄ , 1 ⁄ )-expansion method and determined the exact solution of nonlinear NLEEs.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for finding the exact solutions to nonlinear equations in mathematical physics have been presented, such as the inverse scattering method [1], the Hirota bilinear transform method [2], the truncated Painlevé expansion method [3][4][5][6], the Bäcklund transform method [7,8], the exp-function method [9][10][11], the tanhfunction method [12,13], the Jacobi elliptic function expansion method [14][15][16][17][18], the (G /G)-expansion method [19][20][21][22][23][24][25], the modified (G /G)-expansion method [26], the (G /G, 1/G)-expansion method [27][28][29][30], the modified simple equation method [11,[31][32][33], the multiple expfunction algorithm method [34,35], the transformed rational function method [36], the local fractional series expansion method [37], the first integral method [38][39][40], the generalized Riccati equation mapping method [17,18,41,…”
Section: Introductionmentioning
confidence: 99%